Plant Extract Loaded Nanoparticles - Patihul Husni; Zelika Mega Ramadhania (Indonesian Journal of Pharmaceutics, 2021)
Plant extract, a natural source containing complex mixture of compounds, offers many properties such as antiparasitic, antibiotic, antioxidant, anti-hypertensive, antiviral, insecticide, anticancer, antifungal, hypoglycemic properties. Recent research has been focused on developing formulation the plant extracts not only to deliver them safely but also to enhance its therapeutic efficacy. Nanotechnology-based strategies have been proposed as a system that can be used to formulate plant extracts. Plant extract loaded nanoparticles (NPs) is aimed to facilitate in crossing the biological barriers, to increase bioavailability of poorly water-soluble phytochemicals, to encapsulate mixture compounds of different phytochemicals, to provide targeted delivery of phytochemicals to specific organs resulting in low toxicity, to get effective purification process,  to mask unpleasant taste and odor, to protect sensitive phytochemicals from biological (e.g. enzyme, pH) and environmental (e.g. light, temperature, humidity) degradation, to control release of encapsulated phytochemicals, and to provide a more flexible control over the size and shape of the NPs. This review is focused on plant extract loaded NPs including its advantages, stages for developing formulation of plant extract loaded NPs, and nanosystem used to loading plant extract. In addition, this review also depicts studies which have been conducted by many researchers in developing plant extract loaded NPs. The data were collected from published journals with 21 and 39 journals as primary and supporting literatures, respectively. Plant extracts loaded NPs could be a promising delivery system for active phytochemical contained in the plant extract which is not only to deliver them safely but also to enhance its therapeutic efficacy.Keywords: plant, extract, nanoparticle